ASSESSMENT OF KNOWLEDGE, ATTITUDES AND PRACTICES (KAP) ON MICROBIOLOGICAL SAFETY AMONG CATTLE ABATTOIR WORKERS IN MALAYSIA - MT, Adamu; Garba, Lawal; A.A, Yarma; A.J, Hadiza; A, Mu‟inat A; Isa, Shu‟aibu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Occupational safety and proper meat handling may serve as strategies that can be used to reduce economic loses in the meat industry. Public health can also be improved if the strategies are carefully adhered to. A self-administered questionnaire was distributed to cattle abattoir workers for microbiological safety assessment. The results showed that all the workers have received various forms of training mostly in occupational safety (90%) while only fifty percent (50%) were trained on how to store carcass at the appropriate temperature and how to improve on personal hygiene. Seventy five percent (75%) of workers wear hairnets and ninety percent (90%) cut their finger nails regularly. Respondents within the age of 41-50 scored the highest (60%) compared to 21-30(56%) age groups. Statistical analysis performed using Statistical Package for Social Sciences (SPSS) showed that the mean KAP score was 16.9±2.4 among the workers. The KAP determined by this study highlighted the need for an improvement of workers knowledge on microbiological standards in their working place